Stangersite, a new tin germanium sulfide, from the Katerina mine, Radvanice near Trutnov, Czech Republic - Sejkora,J.; Makovicky,E.; Balic-Zunic,T.; Berlepsch,P. (Journal of Geosciences, 2020)
The new mineral stangersite was found in the burning waste dump of abandoned Katerina coal mine at Radvanice near Trutnov, northern Bohemia, Czech Republic. The new mineral occurs as well-formed, flattened, acicular crystals with a cross-section of 2-5 × 20-40 μm and up to 1 cm in length. They constitute random or fan-shaped clusters on rock fragments and on crumbly black ash in association with greenockite, herzenbergite, unnamed GeS2 and GeAsS. Stangersite was also observed as irregular grains, up to 100 μm in size, in the multicomponent aggregates on which the above-described crystals grow. These aggregates are formed, beside stangersite, by minerals of Bi-Sb, Bi2S3-Sb2S3 and Bi2S3-Bi2Se3 solid solutions, Bi3S2, Bi-sulfo/seleno/tellurides, tellurium, unnamed PbGeS3, Cd4GeS6, GeAsS, GeS2, Sn5Sb3S7, greenockite, cadmoindite, herzenbergite, teallite and Sn- and/or Se-bearing galena. Stangersite formed under reducing conditions by direct crystallization from hot gasses (250-350 °C) containing Cl and F, at a depth of 30-60 cm under the surface of the dump. The mine dump fire started spontaneously and no anthropogenic material was deposited there. Stangersite is brittle (aggregates) or elastic, to flexible (acicular crystals). It is orange to yellowish red with a very light yellowish brown streak, translucent to transparent in transmitted light, and has vitreous to adamantine luster. Cleavage is perfect in two directions: perpendicular and oblique to elongation of crystals. The VHN microhardness is 55 kp·mm-2 (539 MPa) and corresponds to Mohs hardness about 2; the calculated density is 3.98 g·cm-3. In the reflected light, stangersite is light greyish white. Bireflectance and pleochroism were not observed due to distinct orange-brown internal reflections. Anisotropy under crossed polars is strong with dark brownish grey to reddish-brown or brownish violet rotation tints. The empirical formula, based on electron-microprobe analyses of acicular crystals of stangersite, is Sn1.02Ge0.94(S2.93Se0.10)Σ3.03. The ideal formula is SnGeS3, which requires Sn 41.29, Ge 25.25, S 33.46, total 100 wt. %. The chemical composition of stangersite from multicomponent aggregates shows an extensive PbSn-1 substitution covering nearly the whole field of stangersite in the SnGeS3-PbGeS3 solid solution. Stangersite is monoclinic, P21/c, a = 7.2704(15), b = 10.197(2), c = 6.8463(14) Å, β = 105.34(3)°, with V = 489.5 Å3 and Z = 4. The strongest reflections of the powder X-ray diffraction pattern [d, Å/I(hkl)] are: 7.006/100(100), 4.135/49(120), 3.077/47(130), 2.776/38(022), 2.699/69(211), 2.1213/31(320), and 1.7239/35(41-2; 410). Stangersite has a layered structure, with corrugated (100) layers of Sn2+S5 coordination pyramids and with interspaces filled by lone electron pairs of Sn2+ and [001] chains of Ge4+S4 coordination tetrahedra. The Raman spectrum of stangersite with tentative band assignments is given. We named the mineral after its chemical constituents: Sn (stannum), Ge (germanium) and S (sulphur).
Keywords: stangersite; new mineral; tin germanium sulfide; crystal structure; Raman spectroscopy; Radvanice